Lyme Disease Biobank: 10 years of 3 month follow-up visits from 2014 to 2023 - Elizabeth J. Horn; George Dempsey; Anna M. Schotthoefer; Matthew McArdle; Allison F. Weber; Cathy De Luca; Bobbi S. Pritt; Elizabeth L. Maloney (Frontiers in Medicine, 2025)
IntroductionLyme Disease Biobank (LDB) enrolls participants with signs and symptoms of early Lyme disease (LD) from endemic areas and makes samples available to researchers developing more accurate diagnostics. From 2014 to 23, 466 cases and 367 controls were enrolled on Long Island, NY, and in Central Wisconsin.MethodsThis study included 253 LDB participants who provided samples from an initial and a convalescent blood draw. Serologic testing, including a first-tier enzyme immunoassay and IgM and IgG immunoblotting, was performed on all samples; blots were interpreted using CDC criteria.ResultsAt the first draw, 34% of samples from participants presenting with erythema migrans (EM) > 5 cm were positive by CDC’s standard two-tiered testing (STTT) algorithm. IgG seroconversion was rare, only 4% of samples demonstrated seroconversion. While the majority of participants (78%) reported no LD symptoms at the second draw, 22% reported ongoing symptoms; the most common being joint pain, fatigue, and muscle pain. Only 35% of participants with ongoing symptoms reported seeing their provider about their symptoms.ConclusionThese results provide additional evidence that STTT is insensitive in early LD and seroconversion is rare after antibiotics. More than one-fifth of participants initially prescribed antibiotics reported ongoing LD symptoms. Therefore, healthcare professionals treating patients with early LD are encouraged to follow-up with their patients, determine whether they continue to experience symptoms, and consider immediate antibiotic re-treatment as appropriate. Early diagnosis, treatment, and follow-up of early LD patients has the potential to improve outcomes and reduce the burden of LD in the US.